Minilaparotomy cholecystectomy: Presentation, analysis and results of 96 consecutive procedures - Ribero, Gustavo; De Mello, Washington; Cartazzo, J. M.; Sauto, Sergio (Cirugía del Uruguay, 1997)
The authors present casuistry of 96 consecutive cholecystectomies carried out through minilaparotomy of the right hypochondrium performed at the Surgical Service at the Hospital de Rivera between September 1995 and August 1996.